Knee surgery tricks of the trade - Stannard, James P.; Schmidt, Andrew; Kfuri, Mauricio (New York Thieme, 2022)
An indispensable step-by-step guide on a full spectrum of open and arthroscopic knee procedures Knee disorders are among the most common musculoskeletal conditions and, as such, constitute four of the top seven orthopaedic procedures. Currently, 720,000 knee replacements are performed annually in the US, with a projected 3.4 million surgeries by 2030. Knee Surgery: Tricks of the Trade edited by renowned knee surgeons and educators James P. Stannard, Andrew Schmidt, and Mauricio Kfuri features contributions from an impressive cadre of distinguished colleagues. The reader-friendly book fills a g
Description based on online resource; title from PDF title page (Thieme, viewed on April 6, 2022)
Includes index
WorldCat record variable field(s) change: 050, 650
Keywords: Knee -- Surgery; Sports medicine; Orthopedic surgery; Knee -- surgery; Knee Injuries -- surgery; Genou -- Chirurgie; Chirurgie orthopédique.; Electronic books; Electronic books